2005
DOI: 10.1002/chin.200546022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Azaphilones Using Copper‐Mediated Enantioselective Oxidative Dearomatization.

Abstract: Enantioselective syntheses O 0031 Synthesis of the Azaphilones Using Copper-Mediated Enantioselective Oxidative Dearomatization. -(ZHU, J.; GRIGORIADIS, N. P.; LEE, J. P.; PORCO*, J. A. J.; J. Am. Chem. Soc. 127 (2005) 26, 9342-9343; Dep. Chem., Boston Univ., Boston, MA 02215, USA; Eng.) -Nuesgen 46-022

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…31 Racemic syntheses of azaphilones have been reported using these reagents; however, achieving high levels of enantioselectivity can be a challenge. Enantioenriched azaphilones have been accessed using Porco and co-workers' copper-oxo (−)-sparteine dearomatization strategy, 36 achieving the total synthesis of (−)-mitorubrin with 97% ee, 37 as well as that of (+)-sclerotiorin and (+)-8-O-methylsclerotiorinamine from a common precursor obtained in 98% ee. 29 This method requires superstoichiometric quantities of both the oxidant and the chiral ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…31 Racemic syntheses of azaphilones have been reported using these reagents; however, achieving high levels of enantioselectivity can be a challenge. Enantioenriched azaphilones have been accessed using Porco and co-workers' copper-oxo (−)-sparteine dearomatization strategy, 36 achieving the total synthesis of (−)-mitorubrin with 97% ee, 37 as well as that of (+)-sclerotiorin and (+)-8-O-methylsclerotiorinamine from a common precursor obtained in 98% ee. 29 This method requires superstoichiometric quantities of both the oxidant and the chiral ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemistry Although various studies on the synthesis of azaphilones have been reported, some with stereoselective chemistry (26)(27)(28) and others focused on racemic analogues (13,(29)(30)(31)(32)(33), this deceptively simplelooking bicyclic structure still presents significant challenges, especially when the requirement is to prepare analogues with diverse substituents at the 3-position. Recently, Porco's (34) group reported an efficient gold-catalysed cycloisomerization of 2-alkynylbenzaldehydes to give 2-benzopyrylium salts that can subsequently be oxidized with IBX to form the azaphilone ring system.…”
Section: Resultsmentioning
confidence: 99%
“…More recent reports extend the oxidative substrate scope of O species: ortho hydroxylation of phenolic substrates to catechols and quinones, the oxidative reactivity effected by the binuclear copper enzyme tyrosinase [6,8]; oxidation of weak O-H and C-H bonds [7,[35][36][37][38]; catalytic oxidation of cyclohexane to cyclohexanol and cyclohexanone using H 2 O 2 as the oxidant [9] and stoichiometric oxidation of THF to THF-OH and γ-butyrolactone [39], as well as oxidation of toluene to benzyl alcohol [40]. Regioselective and enantioselective oxidative dearomatization reactions (net O-atom transfer) are also possible, including the first asymmetric synthesis of the azaphilone natural products (+)-sclerotiorin and (+)-8-Omethylsclerotiorinamine and the preparation of several unnatural azaphilones, with asymmetric induction achieved using sparteine ligands [41][42][43]. The reactions of characterized O species are joined by numerous catalytic oxidations involving Cu(I) salts and O 2 in which the active oxidant species remain unclear [44].…”
Section: Exogenous Reactivitymentioning
confidence: 99%